Nilai Profetis Pendidikan Islam untuk Menanggulangi Perdagangan Manusia - Sulhan, Moh. (Nadwa, 2012)
Trafficking creates human as commerce object by deception modus, trap, tease, fake appointment, forcing and exploitation, even the violations that insult the human. The Consortium of Indonesia Migrant Labour (KOBUMI) noted that 1-1.5 million from 5 million of Indonesia migrant labours are the victim. American Center for International Labor Solidarity (ACILS) report in 2003 noted that 700.000 to 1 million Indonesia migrant labours who is employable as prostitute. Many of provinces in Indonesia, such as North Sumatra, Riau, Lampung, West Java, Jakarta, Central Java, East Java, West Borneo, East Borneo, North Cele-bes, Bali, and The West Lesser Sundas are the sources of trafficking area. Seeing that trafficking serious problem in Indonesia, it is important to encourage the prevention by adopting many of ethic values as the reinforcement of human re-source and education. Here, Islamic education is important enough to overcome anti-trafficking.